2021
DOI: 10.1590/s1677-5538.ibju.2021.99.02
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic research and diagnosis in bladder cancer: state of the art review

Abstract: Purpose: Proteomic biomarkers have been emerging as alternative methods to the gold standard procedures of cystoscopy and urine cytology in the diagnosis and surveillance of bladder cancer (BC). This review aims to update the state of the art of proteomics research and diagnosis in BC. Materials and Methods: We reviewed the current literature related to BC research on urinary, tissue, blood and cell line proteomics, using the Pubmed database. Findings: Two urinary protein biomarkers are FDA-approved (NMP22® an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The importance of glycomic biomarkers, biomarkers based on the detection of altered glycosylation, for early diagnosis, prognosis, and therapy of many diseases, including cancer, is growing rapidly, and this applies to BC as well. In recent years, there were several published reviews dedicated to the glycan and glycoprotein changes related to BC (Jian et al 2020 ; Jin et al 2021 ; López-Cortés et al 2021 ; Wilson et al 2021 ). In this section, we discuss the newest research on BC glycomic biomarkers that were reported during the last 2 years.…”
Section: Glycomic Biomarkersmentioning
confidence: 99%
“…The importance of glycomic biomarkers, biomarkers based on the detection of altered glycosylation, for early diagnosis, prognosis, and therapy of many diseases, including cancer, is growing rapidly, and this applies to BC as well. In recent years, there were several published reviews dedicated to the glycan and glycoprotein changes related to BC (Jian et al 2020 ; Jin et al 2021 ; López-Cortés et al 2021 ; Wilson et al 2021 ). In this section, we discuss the newest research on BC glycomic biomarkers that were reported during the last 2 years.…”
Section: Glycomic Biomarkersmentioning
confidence: 99%
“…Screening methods for bladder cancer include urine exfoliation cytology, cystoscopy and tumor biomarker assessment ( 9 ). Urine cytology has poor sensitivity for low-grade bladder cancer (sensitivity 25.0-48.0%) ( 10 ). Cystoscopy is the gold standard for diagnosing bladder cancer; however, it is an invasive examination that may lead to risks of bleeding, infection, etc., and easily causes patient discomfort ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proteomics facilitates the elucidation of signaling pathways and the identification of therapeutic targets. Several recent studies have demonstrated the potential of proteomics in the identification of biomarkers and therapeutic targets in urogenital cancers, highlighting the importance of conducting further research in clinical settings [ 13 , 14 , 15 ]. While a number of studies on the role of proteomics in urogenital cancers have begun to be published, a comprehensive synthesis and analysis of these findings is lacking.…”
Section: Introductionmentioning
confidence: 99%